Nottinghamshire introduction - Thorn, Frank; Thorn, Caroline (The University of Hull)
The introduction discusses the history of the county and its assessment; the county boundary; the administration of the county; the Wapentakes, their reconstruction, rubrication, order, revised name-forms, and boundaries; small Hundreds; Wapentake courts, moot-sites, links to royal manors, and lordship; later Wapentakes; manorial and ecclesiastical organisation; the state of the manuscript for the county; content and layout of entries; writing and revision; Rutland; duplicate entries; boroughs, castles and Forest; the identification of places; the editorial history of earlier versions of the notes, and the current state of the revision. The introduction has been written for this edition by Caroline and Frank Thorn.